2022
DOI: 10.2147/ijn.s374247
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Responsive Smart Implantable Hydrogels for Targeted Delivery of Drugs: Reviewing Current Practices

Abstract: Over the last two decades, the process of delivering therapeutic drugs to a patient with a controlled release profile has been a significant focus of drug delivery research. Scientists have given tremendous attention to ultrasound-responsive hydrogels for several decades. These smart nanosystems are more applicable than other stimuli-responsive drug delivery vehicles (ie UV-, pH-and thermal-, responsive materials) because they enable more efficient targeted treatment via relatively non-invasive means. Ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 150 publications
0
10
0
Order By: Relevance
“…These two effects can be utilized to de-cross-link the polymeric networks. 175 When a hydrogel is designed with reversible cross-linking chemistry or a self-healing system, a trigger-on-demand release system could be envisioned. A zinc-oxide-loaded ultra-stretchable hydrogel was synthesized by polymerizing N , N -dimethylacrylamide (DMA), and methacrylic acid (MAA), which can adhere to the abdominal cavity and provide excellent contrast for ultrasound imaging of changes in organ size.…”
Section: Stimuli-responsive Hydrogelsmentioning
confidence: 99%
“…These two effects can be utilized to de-cross-link the polymeric networks. 175 When a hydrogel is designed with reversible cross-linking chemistry or a self-healing system, a trigger-on-demand release system could be envisioned. A zinc-oxide-loaded ultra-stretchable hydrogel was synthesized by polymerizing N , N -dimethylacrylamide (DMA), and methacrylic acid (MAA), which can adhere to the abdominal cavity and provide excellent contrast for ultrasound imaging of changes in organ size.…”
Section: Stimuli-responsive Hydrogelsmentioning
confidence: 99%
“…Generally, ultrasound waves have applications in different fields, such as in vivo imaging, physiotherapy, cosmetics and food industry [ 216 ]. In general, release systems based on ultrasound waves are obtained from polymers, in different forms, such as polymer-coated bubbles/emulsions, and polymer hydrogels [ 216 , 217 , 218 , 219 , 220 ]. It was reported that ultrasonic-responsive drug delivery systems are able to increase drug delivery, but also increase the therapeutic efficacy, and temporal release of drugs [ 221 ].…”
Section: External Stimuli-responsive Drug Delivery Systemsmentioning
confidence: 99%
“…Hydrogels are three-dimensional water-swollen networks with hydrophilic nature crosslinked by various hydrophilic polymers via chemical covalent bonds, physical non-covalent bonds or a combination of both. [1][2][3][4] Meanwhile, hydrogels could be further classified as natural, synthetic or hybrid Wei Huang Prof. Wei Huang serves as the Director of the Department of Orthopedics at the First Affiliated Hospital of Chongqing Medical University, where he also holds the position of Director of the Orthopedics Laboratory. Additionally, he holds the position of Vice President of the Orthopedic Physicians Branch of the Chinese Medical Association.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are three-dimensional water-swollen networks with hydrophilic nature crosslinked by various hydrophilic polymers via chemical covalent bonds, physical non-covalent bonds or a combination of both. 1–4 Meanwhile, hydrogels could be further classified as natural, synthetic or hybrid based on the source of constituting materials. 4–6 Due to their excellent biocompatibility, extracellular matrix (ECM)-like structure and immensely tunable properties (modified through physical/chemical methods) for specific applications, hydrogels are one of the most widely utilized soft biomaterials in tissue engineering (providing mechanical support and scaffold for tissue regeneration, transporting drugs/cells/cytokines/bioactive molecules, etc .).…”
Section: Introductionmentioning
confidence: 99%